The role of Executive Functions in people with Autism Spectrum Disorder - Roberta Minino (Firenze University Press, 2022)
Executive functions involve a set of complex cognitive abilities that have the task of programming and controlling other cognitive functions and modifying them according to circumstances in order to achieve a goal. They thus regulate cognitive processes, behaviour, and the management of emotions. It is now known that all mechanisms managed by executive functions are affected in numerous neurodevelopmental disorders, including Autism Spectrum Disorder. In fact, it presents a variable symptomatology, affecting various cognitive, behavioural, motor and sensory aspects. The aim of this work was to delve into the subject of executive functions, and above all to analyse and explain the close link between executive functions and Autism Spectrum Disorder. Based on previous studies, this work shows a clear link between them. In particular, it appears that Autism Spectrum Disorder presents moderate deficits in all sub-domains of Executive Functions, and in particular visuospatial and inhibition-related Working Memory, and interference control. However, the literature still shows conflicting results, and further studies are needed to thoroughly evaluate the different subdomains of Executive Functions and the different forms of Autism Spectrum Disorder.   Il ruolo delle Funzioni Esecutive in persone con Disturbo dello Spettro Autistico Le funzioni esecutive riguardano un insieme di abilità cognitive complesse il cui compito è quello di programmare e controllare altre funzioni cognitive e modificarle in base alle circostanze, al fine di raggiungere uno scopo. Esse regolano i processi cognitivi, il comportamento, e la gestione delle emozioni. È ormai noto che i meccanismi gestiti dalle funzioni esecutive, sono coinvolte nei disturbi del Neurosviluppo, tra cui il Disturbo dello Spettro Autistico. Infatti esso presenta una sintomatologia che riguarda diversi aspetti cognitivi, comportamentali, motori e sensoriali. L'obiettivo di questo lavoro è stato quello di approfondire l'argomento delle funzioni esecutive, e soprattutto quello di analizzare lo stretto legame che intercorre tra Funzioni Esecutive e Disturbo dello Spettro Autistico. Sulla base di studi precedenti, questo lavora evidenza un chiaro legame tra di essi. In particolare, il Disturbo dello Spettro Autistico presenta dei deficit moderati in tutti i sottodomini delle Funzioni Esecutive, ed in particolare della Memoria di Lavoro Visuo-Spaziale e quella legata al Controllo delle Interferenze. Tuttavia la letteratura mostra ancora risultati contrastanti, e necessita di ulteriori approfondimenti che vadano ad indagare i diversi sottodomini delle funzioni esecutive e le diverse forme di Disturbo dello Spettro Autistico.